Temperature Affects the Germination of Forage Legume Seeds. Issue 6 (1st November 2014) - Butler, Twain J.; Celen, Ahmet E.; Webb, Stephen L.; Krstic, Djordje; Interrante, Sindy M.
ABSTRACT: Temperature, in addition to moisture, oxygen, and light, plays an important role in seed germination. Early seedling emergence and stand establishment can be promoted by germination of seeds under a wide range of temperatures; therefore, it is desirable for commercial legume cultivars to germinate over a range of temperatures. The objective of this growth chamber experiment was to determine the effects of temperature on seed germination of seven annual warm‐season and 11 annual cool‐season legumes. Greatest germination of warm‐season and cool‐season legumes occurred at 25 and 20°C, respectively. Germination of warm‐season legumes tended to be maximized at 25°C, while cool‐season legume germination was greatest from 10 to 25°C. Cultivars 'Rio Verde' lablab [ Lablab purpureus (L.) Sweet] and 'Whitetail Thicket' soybean [ Glycine soja Siebold and Zucc. × Glycine max (L.) Merr.] had greater germination than the other entries at 35°C, indicating their potential for use in warmer climates or in delayed planting dates. Additionally, Whitetail Thicket had the greatest germination of summer legume entries at 10°C. The germination of 'Dixie' crimson clover ( Trifolium incarnatum L.), PI 419238 button medic [ Medicago orbicularis (L.) All.], and 600RR and 'Bulldog 505' alfalfas ( Medicago sativa L.) were less sensitive to temperature than the other cool‐season legume entries. Germination of 'Devine' little burr medic ( Medicago minima L.), 'Armadillo' burr medic ( Medicago polymorpha L.), and 'Apache' arrowleaf clover ( Trifolium vesiculosum Savi) were severely reduced at temperatures above 30°C.